Studies in Deuteronomy : in honour of C.J. Labuschagne on the occasion of his 65th birthday - Labuschagne, C. J.; García Martínez, Florentino. (Supplements to Vetus Testamentum,, 1994)
Studies in Deuteronomy was compiled as a respectful tribute to Professor C.J. Labuschagne and was presented to him on the occasion of his 65th birthday. The choice of the book of Deuteronomy as a fitting topic for a collection of commemorative essays reflects the focus of Professor Labuschagne's own research on this part of the Bible in recent years. The essays, which employ a variety of methodological approaches to the study of Deuteronomy, deal with such subjects as Masoretic, Septuagintal and Qumran variations in the text of Deuteronomy, Deuteronomic elements in other biblical books, and the reception history of Deuteronomy in the Jewish and Christian worlds. Included also is a first edition of some Deuteronomy manuscripts from Qumran, Masada and Nahal Hever.